THE EFFECT OF BRAND IMAGE, EWOM, PRODUCT QUALITY, AND PRICE ON PURCHASE INTENTION OPPO SMARTPHONE IN JAKARTA - Pramudya Gusti Kelana; Galuh Mira Saktiana (International Journal of Application on Economics and Business, 2026)
The purpose of this research is to examine brand image, EWOM, product quality, and price influence the purchase intention of Oppo smartphones among the people of DKI Jakarta. The sample consisted of 250 respondents who are consumers aware of Oppo smartphones in the DKI Jakarta area. Purposive sampling, with data collected through an online questionnaire distributed via Google Forms. The collected data were analyzed using the Structural Equation Modelling (SEM) method and processed with the SmartPLS application. The results of the study indicate that brand image, electronic word of mouth, product quality, and price all have a positive influence on purchase intention. Specifically, the findings show that: (1) brand image has a positive significant on purchase intention, (2) EWOM has a positive and significant effect on intention to buy, (3) product quality has a positive not significant effect on purchase intention, and (4) price has a positive but not significant effect on purchase intention. These findings suggest that brand image and e-WOM play a dominant role in driving the purchase intention of consumers in DKI Jakarta toward Oppo smartphones. Furthermore, although product quality and price have a positive impact, they are not significant, indicating that purchase decisions are more strongly influenced by brand perception and consumer reviews on social media. This highlights the importance of branding strategies and effective e-WOM management in increasing purchase intention.